Analysis Factors Correlated with the Incidence of Retained Placenta to Vaginal Birth Mother at Aura Syifa Hospital of Kediri Regency - Ira Titisari; Henny Lathifatuzzahro; Ribut Eko Wijanti (JURNAL KEBIDANAN, 2020)
Retained placenta is a placenta which is not born more than 30 minutes after the birth. Predisposing factors of retained placenta are placenta previa, former cesarean section, repeated curettage and gemelli. The incidence of retained placenta in Aura Syifa Hospital of Kediri Regency in 2015 was 71 (4.78%) cases from 1483 births and in 2016 increased to 101 (5.22%) cases from 1935 births. The purpose of this research was to know the correlation between age, parity, birth spacing, and history of cesarean section with retained placenta incidence in Aura Syifa Hospital of Kediri Regency. The method of this study used case-control design with 84 (case) and 294 (control) samples. The instrument was medical record maternal in 2012. The analysis of this study used univariate and bivariate analysis with odds ratio test. The conclusions of the study, factors that increased the incidence of retained placenta were age, parity, birth spacing and history of cesarean delivery. In the future, further examination is needed to identifying the other factors that cause retained placenta such as multiple pregnancy, history of curettage, history of retained placenta, placenta previa and gestational age.